Perbedaan Tingkat Kecukupan Energi Protein, Status Kesehatan Dan Status Gizi Anak yang Memanfaatkan dan Tidak Memanfaatkan Makanan Sekolah Dasar Islam Terpadu (SDIT) Harapan Bunda Semarang - Exsi Rila Kusuma; Agus Sartono; Hapsari Sulistya Kusuma (Jurnal Gizi, 2016)
The Children, included school-age (6-12 years old) is a children period who do not understand a balanced nutrition yet, generally. It causes they do fault in selecting meals. The condition can make they suffer malnutrition problem, School meals service in Islamic Primary School (SDIT)Harapan Bunda Semarang intended to solve a problem related to the school meals in school children. The purpose to be achieved is to reduce student eating randomly snack so that decrease the risk of diseases which is caused from food and to adequate nutrition intaketo increase childrens nutritional status and health.This aims of the research is to analyze the difference of protein energy sufficiency level nutritional status and health status between the children who apply and not apply school meals atIntegrated Islamic Primary School (SDIT) Harapan Bunda Semarang.The type research is analytic with observation method and cross sectional approach. The research samplings are 108 students of 3 th, 4 rd and 5 th class of SDIT Harapan Bunda Semarang.The samplings are taken by stratified random sampling. The correlation of variables are analyzed with Mann-Whitney test (Z test)and Chi-Square test.Quality of school meals has been good qualified in terms of acceptability, but not good in menu variations and nutrition content yet. Moreover, there is no difference of energy sufficientlevels (pv : 0.415) between children who apply and not apply school meals. There are no difference of protein sufficient levels (pv : 0,289), no defference of health status (X : 0,282)and no defference of nutritional status (pv : 818) between children who apply and not apply school mealsThere is no difference of energy protein sufficient level, health status and nutritional status between the children who apply and not apply school meals at Integrated Islamic PrimarySchool Harapan Bunda Semarang.Key Word: School-Age Children, Quality of School Meals, Protein Energy Sufficient Level, Health Status and Nutritional status